EFFECT INTERACTION BETWEEN INOCULATION FUNGUS TRICHODERMA harzinum AND VEGETATION FERTILIZATION ALGAE CHARA SP. AND CHEMICAL IN PLANT GROWTH ONION (ALLIUM cepa L.). - Suhail , Faris M. (Diyala Agricultural Sciences Journal, 2013)
A factorial Experiment was conducted in sandy loam soil, using a complete randomization design (CRD), in College of Agriculture – University of Diyala in plastic bags to assess effect treatment of fungi Trichoderma harzianum and alga Chara sp, chemical fertilizers and the interaction between them in the onion plant growth. The results showed that added dual (Trichoderma harzianum + Chara sp ) led to a significant increase in both plant height ,length roots , Number of leaves, diameter bulb and wet weight and dry (32.58 cm, 40.0 cm, 6.92 leaf -1, 1.48 cm, 32.67 g. Plant -1,11.13 g. plant -1), respectively, and irrespective of the addition of chemical fertilizers. They gave treatment double (Trichoderma harzianum + Chara sp) and interaction with the level 50% of chemical fertilizers higher values for all studied traits and increase significantly was (21.73%, 71.66%, 65.0%, 61.90%, 30.76%, 60.0%), respectively, compared to the treatment comparison and at the level of 50%. The treatment added double (Trichoderma harzianum + Chara sp) and at the level of 50% of chemical fertilizers is the preferred treatment and Trichoderma harzianum and Chara sp saving 50% of the amount of chemical fertilizers.